The Effectiveness Of Red Power Injection On The Hematological Profile Of Layer Chicken (Gallus domesticus) - Lazwari, Rahamaddanu Surya; Yasmin, Anandira Dania; Lutfiah, Fatun Latifa; Fahmi, Zarkasya Zahra Nur Saffanah; Nugroho, Zatya Dimas Prakoso; Dewa, Gogod Wahyu; Eros, Easter Palma Dewi; Fadhila, Azzahra Shafa Fadhila (Universitas Airlangga, 2024)
Layer chickens are one of the most popular types of mass-produced laying hens in Indonesia. One way to keep laying hens healthy is to fulfill their micronutrient and vitamin needs. Giving vitamins such as Red power injection is very good for broilers, layers and fighters. Red power injection contains extra liver which contains vitamin B12, folic acid, and iron which are useful for maintaining chicken health. In this study, researchers wanted to test the effectiveness of Red power injection supplements in increasing blood in laying hens (Gallus domesticus). The study used an experimental research method using two treatments for one day. Four laying hens (Gallus domesticus) that have been provided are divided into two treatment groups with a dose of group one 0.8 ml / head and a dose of group two 1.2 ml / head. The variable observed was the increase of Hematology Profile (Erythrocytes, Leukocytes, and Hemoglobin). The results showed an increase in the Hematology Profile tested. The increase in the Hematology Profile is due to the effect of nutrition on chickens has been fulfilled, Red power injection is a supplement containing liver extract which helps the formation of Hematology Profile in Laying Hens (Gallus domesticus).